DESENTRALISASI DAN PENGANGGARAN OBAT PADA DINAS KESEHATAN KABUPATEN PROPINSI NUSA TENGGARA TIMUR (NTT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: Drugs play a very important role in managing and improving health status. The local income (PAD) and general allocation fund (DAU) that are limited and the views of local authority (PEMDA) and district house of common (DPRD) on health that is considered as a consumptive sector is the main problem in ensure the sustainability of drugs financing in time of decentralization. This study was aimed at finding out the budgeting and quality of drugs planning in the District Health Office in the era of decentralization. Methods: This was a descriptive explorative study using qualitative and quantitative data. The study was held in East Nusa Tenggara (NTT). The analysis units were District Health Office (DKK) chosen purposively, i.e. South Central Timor (TTS) representing DKK with P2M intensification projects